VEGETATIVE SUPPORT OF CARDIAC ACTIVITY IN ATHLETES WITH DIFFERENT ANTHROPOMETRIC PROFILE - O. N. Kudrya (Бюллетень сибирской медицины, 2016)
The purpose of research – to study the features of the functioning of the cardiovascular system and regulatory mechanisms of the young athletes of different heights.Materials and methods. The study included athletes aged 15-16 (32 girls and 36 boys) engaged in competitive sports. To study the autonomic regulation of the cardiovascular system using mathematical methods and spectral analysis of heart rate variability. To characterize the vegetative support the circulatory apparatus, all subjects performed an active orthostatic test.Results. The features of vegetative maintenance of heart activity in tall athletes: stress regulatory mechanisms observed resting in tall men and decrease the functionality of the sympathetic division of the autonomic nervous system during active orthostatic test in athletes of different sex. Athletes tall urgent adaptation of the cardiovascular system to changing external conditions associated with activation of suprasegmental divisions of the autonomic nervous system and the excessive activation of the sympathetic division, which is an inefficient way of adaptation.Conclusion. Thus, high growth is evident not only in the increase of total size of the body of athletes, but also in the peculiarities of morphofunctional state involved, indicating the need of individual rationing of loads for tall players. The revealed morphofunctional characteristics of the organism tall athletes allow us to recommend an increase in the proportion of aerobic exercise to enhance the adaptive capacities of the organism.